Restructuring Family Policies : Convergences and Divergences - Baker, Maureen (Book collections on Project MUSE., 2006)
"Drawing from nation-based research, cross-national studies, and international databases, Restructuring Family Policies successfully integrates mainstream academic debates about restructuring welfare states with feminist research findings and current policy concerns."--Jacket